Association of the British Athletic Muscle Injury Classification and anatomic location with return to full training and reinjury following hamstring injury in elite football. Issue 2 (10th May 2021) - Shamji, Ricky; James, Steven L J; Botchu, Rajesh; Khurniawan, Kent A; Bhogal, Gurjit; Rushton, Alison
Abstract : Background: The relationship between hamstring muscle injuries (HMIs) that involve the intramuscular tendon and prolonged recovery time and increased reinjury rate remains unclear in elite footballers. Objective: To determine the association of time to return to full training (TRFT) and reinjury of HMIs using the British Athletic Muscle Injury Classification (BAMIC) and specific anatomical injury location in elite-level football players. Methods: The electronic medical records of all players at an English Premier League club were reviewed over eight consecutive seasons. All players who sustained an acute HMI were included. Two experienced musculoskeletal radiologists independently graded each muscle using the BAMIC, categorised each injury location area (proximal vs middle vs distal third and proximal vs distal tendon) and reported second muscle involvement. TRFT and reinjury were recorded. Results: Out of 61 HMIs, the intramuscular tendon (BAMIC 'c') was involved in 13 (21.3%). HMI involving the intramuscular tendon ('c') had a mean rank TRFT of 36 days compared with 24 days without involvement (p=0.013). There were 10 (16.4%) reinjuries with a significant difference of 38.5% reinjury rate in the group with intramuscular tendon injury ('c') and 12.5% in the group without (p=0.031). TRFT and reinjury involving a second muscle was statistically significantly higher than without. Most of the HMIs to the biceps femoris with reinjury (5 out of 9) were in the distal third section related to the distal tendon site involving both the long and short head. Conclusion: TRFT in HMI involving the intramuscular tendon ('c') of the Biceps femoris is significantly longer with significantly higher reinjury rate compared with injuries without, in elite football players. The finding that most reinjures of the biceps femoris occurring in the distal third muscle at the distal tendon site, involving both the long and short head, merits further investigation.